Differential Functions of Two Metalloproteases, Mrmep1 and Mrmep2, in Growth, Sporulation, Cell Wall Integrity, and Virulence in the Filamentous Fungus Metarhizium robertsii - Zhou, Rong; Zhou, Xiazhi; Fan, Ali; Wang, Zhangxun; Huang, Bo (Frontiers in Microbiology, 2018)
The Metarhizium genus of filamentous entomopathogenic fungi plays a pivotal role in regulating insect populations. Metalloproteases are a widely distributed and diverse family of hydrolytic enzymes that are important toxicity factors in the interactions between fungi and their hosts. Herein, we characterized two metalloproteases, Mrmep1 and Mrmep2, in Metarhizium robertsii using gene deletion. The growth rates of the resulting Mrmep1 and Mrmep2 mutants were decreased by 16.2% and 16.5% relative to the wild-type (WT) strain. Both mutants were less sensitive to cell wall stress using sodium dodecyl sulfate and Congo red reagents, whereas sensitivity to UV-B irradiation and heat stress were not affected. Sporulation analysis revealed that the conidial yield in Mrmep1, Mrmep2, and Mrmep1Mrmep2 mutants was reduced by 56.0%, 23%, and 53%, respectively. The bioassay analysis showed that LT50 values against Galleria mellonella were decreased by 25.5%, 19%, and 28.8% compared with the WT strain suggesting attenuated fungal virulence in the Mrmep1 and Mrmep2 strains. The result of quantitative reverse transcription-PCR showed that mRNA expression levels of Mrmep1 was higher than Mrmep2 during infection. Additionally, mRNA expression levels of gallerimycin were 1.2-fold, 2.18-fold and 2.5-fold higher in insects infected with Mrmep1, Mrmep2 and the Mrmep1Mrmep2 mutant, respectively, compared with the WT strain. These results suggested that Mrmep1 and Mrmep2 were involved in the growth, sporulation, cell wall integrity and virulence of M. robertsii.